Emotional intelligence training as a protective factor for mental health during the COVID‐19 pandemic. Issue 10 (22nd July 2021) - Persich, Michelle R.; Smith, Ryan; Cloonan, Sara A.; Woods‐Lubbert, Rebecca; Strong, Michael; Killgore, William D. S.
Abstract: Introduction: The COVID‐19 pandemic has presented a major challenge to mental health and emotional wellbeing. The present study examined whether training in emotional intelligence (EI) skills, provided before the pandemic, would serve as a protective factor for sustaining mental health during the COVID‐19 crisis. Methods: Data came from a longitudinal study ( N = 89) that was initially designed to test the effectiveness of an EI training program versus a non‐emotion‐focused placebo program. The design and timing of the study were such that baseline and posttraining assessments of depression and anxiety had been completed before the pandemic, and planned 6‐month follow‐ups were serendipitously scheduled to occur after the onset of the COVID‐19 crisis. This provided us with an unexpected real‐world opportunity to investigate whether EI training would bolster emotional resilience to the challenges posed by the COVID‐19 pandemic. Results: Although mental health concerns generally increased after the start of the pandemic, individuals who completed the EI training program scored lower on depression, suicidal ideation, and state anxiety relative to individuals who had been assigned to the placebo training program. Conclusion: Online EI training appears to be effective at sustaining critical aspects of mental health during a subsequent real‐life crisis.